Metformin induces weight loss associated with gut microbiota alteration in non-diabetic obese women: a randomized double-blind clinical trial. Issue 3 (March 2019) - Ejtahed, Hanieh-Sadat; Tito, Raul Y; Siadat, Seyed-Davar; Hasani-Ranjbar, Shirin; Hoseini-Tavassol, Zahra; Rymenans, Leen; Verbeke, Kristin; Soroush, Ahmad-Reza; Raes, Jeroen; Larijani, Bagher
Abstract : Objective: The increasing prevalence of obesity over the past few decades constitutes a global health challenge. Pharmacological therapy is recommended to accompany life-style modification for obesity management. Here, we perform a clinical trial to investigate the effects of metformin on anthropometric indices and gut microbiota composition in non-diabetic, treatment-naive obese women with a low-calorie diet (LCD). Design: Randomized double-blind parallel-group clinical trial Methods: Forty-six obese women were randomly assigned to the metformin (500 mg/tab) or placebo groups using computer-generated random numbers. Subjects in both groups took two tablets per day for 2 months. Anthropometric measurements and collection of blood and fecal samples were done at the baseline and at the end of the trial. Gut microbiota composition was assessed using 16S rRNA amplicon sequencing. Results: Twenty-four and twenty-two subjects were included in the metformin + LCD and placebo + LCD groups, respectively; at the end of trial, 20 and 16 subjects were analyzed. The metformin + LCD and placebo + LCD caused a 4.5 and 2.6% decrease in BMI from the baseline values, respectively ( P < 0.01). Insulin concentration decreased in the metformin + LCD group ( P = 0.046). The overall fecal microbiota composition and diversity were unaffected in the metformin + LCD group. However, a significant specific increase in Escherichia/Shigella abundance was observed after metformin + LCD intervention ( P = 0.026). Fecal acetate concentration, but not producers, was significantly higher in the placebo + LCD group, adjusted for baseline values and BMI ( P = 0.002). Conclusions: Despite the weight reduction after metformin intake, the overall fecal microbiota composition remained largely unchanged in obese women, with exception of changes in specific proteobacterial groups.